Literature Review: Green Satisfaction - Wiwik Handayani; Reiga Ritomiea Ariescy; Hendro Widjanarko; Felia Ananda Cahya; Salsabila Islami Yusnindi; Roudlotul Badi’ah (Nusantara Science and Technology Proceedings, 2021)
The purpose of this literature review is to review and explore the results of previous studies and other literature related to green satisfaction. The research method used is a literature review. Green satisfaction indicates that people are pleased with the environmental conditions around their homes. The results of the previous studies indicate that environmental cleanliness has a significant role in building green satisfaction. To maintain green satisfaction, the community needs to help each other to keep the environment clean. A clean environment also has a good impact on health. If the environment is a slum, the worst possibility that will happen is the relocation of residents by some people towards a better place to live. In this case, green satisfaction will reappear and increase if the new location is healthy and clean. People are even willing to pay more to get the satisfaction of being in a clean environment.